Design of density and density calculator as a basic physics experiment tool - Radhy, Ahmad; Nugraha, Wildan Irsa (Faculty of Vocational Studies - Research Center, DRPM ITS, 2024)
One of the characteristics of liquid fluid is that it has a density. Many research methods have been carried out on this case, therefore in this study a simple method of measuring density was developed accompanied by a specific gravity connected via PC. The prototype consists of a loadcell sensor with the HX711 module which can convert the change in strain or resistance into a form of tension, a flow sensor is used to measure the volume of a liquid fluid through the input debit of liquid fluid flow in the measuring cup, and a mini pump equipped with a high and low relay mode with a voltage of 12 volts. The object of this study uses 3 types of fluids namely water, sugar water, and salt water. Measurement experiments were carried out by injecting the liquid by turning on the pump using the start button on the interface and pressing the stop button when it reaches the desired setpoint. Data from the volume of the liquid is obtained then compared with the results of density and specific gravity measurements theoretically. From the results of calculations and data analysis of 3 liquid fluids using static characteristics, the error value is 4,14% for water, 11,25% for sugar solution, dan 23,5% for salt solution.